การหาจลนพลศาสตร์ในการยับยั้งเมตาบอลึซึมของไขมัน โดยสารสำคัญที่แยกได้จากพืชสมุนไพรในพื้นที่ของโครงการอนุรักษ์พันธุกรรมพืช อันเนื่องจากพระราชดำริฯ บริเวณเกาะแสมแสมสาร จังหวัดชลบุรี : รายงานผลการดำเนินงาน - ทักษิณา ชวนอาษา (จุฬาลงกรณ์มหาวิทยาลัย, 2015)
The research is to study kinetic of the pancreatic lipase enzyme in the presence of a hexane extract of Lum Bid Dong (Diospyros filipendula) leaves harvested from the Plant Genetic Conservation Project area under The Royal Initiative of Her Royal Highness Princess Maha Chakri Sirindhorn, Samae-San Island, Chonburi. The previous study showed that uvaol was isolated from ethyl acetate extracts of Lum Bid Dong and exhibited pancreatic lipase actiivity. This chemical was unstable under our storage condition leading to an unsuccessful kinetic study of the enzyme in the presence of uvaol. However this substance was also found in the hexane extract which presented 94.95 ± 2.92% pancreatic lipase inhibitory activity with 1 mg/mL final concentration. The IC50 value of this extract was 0.24 mg/mL. Kinetic study of the enzyme was performed in the presence of the hexane extract which showed non-competitive inhibition by Lineweaver-Burk plot analysis. Under a controlled condition, Km value for enzyme was 808.09 μM and Vmax was 23.53 μM min-1. In the presence of the hexane extract, Vmax was 13.57 μM min-1 and 15.72 μM with 0.5 and 0.25 mg/mL final concentration, respectively. Further isolatation is required to determine active compounds essentially responsible for this activity. Obtained active substances will be informative for development and modeling of a new anti-lipid metabolism drug in the future.